Protestantes, curanderos y descreídos. Misiones interiores, religiosidad nacional-católica e intolerancia durante el primer franquismo, 1940-1960 - Francisco Bernal García (Cahiers de Civilisation Espagnole Contemporaine)
The internal missions were one of the main manifestations of National-Catholic religiosity. These pastoral interventions also had a coactive dimension –as they sought to exclude from public life any behaviour that was incompatible with the Catholic faith– and a coercive dimension –as they incorporated mechanisms designed to ensure that those who did not wish to do so joined in the missionary activities. In this sense, they can be interpreted as manifestations of religious intolerance and as instruments of pressure on those social groups that did no fit in with the National-Catholic ideal of Spanishness. This article explores this interpretation by analysing three aspects of the missionaries’ actions: their efforts to harass Protestant communities; their struggles against quackery and other manifestations of the «common religion»; and the pressures they exerted against those who claimed to have no religious beliefs of any kind.